2009
DOI: 10.1001/archoto.2009.99
|View full text |Cite
|
Sign up to set email alerts
|

Bone-Anchored Hearing Aid Implant Location in Relation to Skin Reactions

Abstract: Implant location and skin thickness were not correlated with implant loss or the frequency or degree of adverse skin reactions around the abutment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 26 publications
5
36
1
Order By: Relevance
“…However, neither study [34] examined the effect of varied soft tissue thickness at the implant site, which is known to differ considerably among patients [9]. Thus, the degree to which stimulation was reduced with varying soft tissue thickness was not explored.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, neither study [34] examined the effect of varied soft tissue thickness at the implant site, which is known to differ considerably among patients [9]. Thus, the degree to which stimulation was reduced with varying soft tissue thickness was not explored.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the degree to which stimulation was reduced with varying soft tissue thickness was not explored. A recent study by Faber et al revealed significant variability in soft tissue thickness (2–11 mm, mean of 5.5 mm) over a proposed implant site among 204 patients [9]. The importance of soft tissue thickness on stimulation effectiveness is therefore of critical importance to the surgeon when implanting the device.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If all of these precautions are taken into consideration and therapy-resistant skin reactions still occur, recent studies have shown that changing to a larger 8.5-mm abutment can be beneficial [45][46][47]. A recent study by Faber et al [48] showed that implant location was not correlated with the frequency and severity of skin reactions around the abutment in 248 randomly selected Baha patients.…”
Section: Goals Of Surgerymentioning
confidence: 99%
“…Children have a higher rate of implant loss [11]. Faber et al [12] propose the cause of the higher extrusion rate in children is that the child's skull is thinner and has a lower mineral content compared to the adult skull. Skull thickness is not just dependent on age, but also related to craniofacial abnormalities such as in Treacher-Collins' syndrome [13].…”
mentioning
confidence: 99%